Functional microRNA screening for dietary vitamin E regulation of abdominal fat deposition in broilers. Issue 4 (3rd July 2020) - Zhang, M.; Liu, L.; Chen, D.; Zhang, X.; Zhou, C.; Gan, Q.; Li, Y.; Wu, Q.; Li, H.; Xu, W.; Zhang, M.; Huang, Q.; et al.
ABSTRACT: 1. Functional microRNA (miRNA) screening for abdominal fat tissue with different dietary vitamin E (VE) levels was performed to reveal miRNAs, genes and metabolic pathways involved in abdominal fat deposition in broilers. 2. A total of 240, one-day-old healthy female chicks were randomly allocated into five dietary treatments containing either 0, 20, 50, 75 or 100 IU DL-α-tocopherol acetate. The sequencing of miRNAs from abdominal fat tissues was performed. The target genes of miRNAs were predicted and enrichment analysis for these genes was performed. Diets supplemented with 50 IU VE significantly diminished abdominal fat deposition in broilers at day 35 of age. 3. A total of 29 miRNAs were differentially expressed between control and 50 IU VE treatment. Ten of the 23 target genes were enriched in four signalling pathways: tight junction, SNARE interactions in vesicular transport, regulation of autophagy and proteasome. 4. This study identified miRNA, target genes and pathways in dietary VE treatment for broilers, providing new insights into the miRNA regulation of abdominal fat deposition in broilers.